Toward a scalable and collaborative network monitoring overlay - Castro, Vasco (2011)
This paper presents ongoing work toward the definition of a new network monitoring model which resorts to a cooperative interaction among measurement entities to monitor the quality of network services. Exploring (i) the definition of representative measurement points to form a network monitoring overlay; (ii) the removal of measurement redundancy through composition of metrics; and (iii) a simple active measurement methodology, the proposed model aims to contribute to a scalable, robust and reliable end-to-end monitoring. Besides the model proposal, a JAVA prototype was implemented to test the conceptual model and its design goals.